To solve the equation \((x - 1)(2x + 5) = 0\) using the Zero Product Property, we need to set each factor equal to zero.
-
Set the first factor equal to zero: \(x - 1 = 0\) \[ x = 1. \]
-
Set the second factor equal to zero: \(2x + 5 = 0\) \[ 2x = -5 \] \[ x = -\frac{5}{2}. \]
Thus, the values of \(x\) that make the quadratic equation equal to zero are: \[ x = 1 \] and \[ x = -\frac{5}{2}. \]
From the options given, the correct answer is:
The quadratic equation will equal zero when x equals negative 5 over 2 and x equals 1.